Implementasi Sistem Informasi Pencatatan Laporan Tahfiz pada Yayasan Majelis Hifzhu Syifaa Cileungsi - Dedi Gunawan; Hakim Mora; Husein; Abdullah Fathan Hafidzurrahman; Safira Berliani (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2023)
This article discusses the implementation of the website based Tahfiz Report Recording Information System application at the Assembly Hifzhu Syifaa Cileungsi Foundation because of community service activities. The main purpose of implementing this application is to make it easier for the Foundation to manage and record the students' memorization reports. This website-based application allows teachers to easily enter grades and notes related to students' memorization through the application, thereby speeding up the recording and assessment process. This application can be accessed via a web browser, providing access flexibility for users. In application development, special attention is paid to a simple user interface to make it easy for novice users to use. The research method used is descriptive qualitative with data collection through questionnaires and research. The development technique applied is Prototype, where application functions are tested with relevant input. The results of this implementation present a website based Tahfiz Report Recording Information System application as a practical solution for the Assembly Hifzhu Syifaa Cileungsi Foundation in managing rote reports. It is hoped that this application will provide significant benefits and can be adopted by foundations or similar institutions that require an effective and efficient tahfiz report recording system.